Devonian deltaic facies of Jaciara-Mato Grosso: Indication of a new stratigraphic proposal for the Alto Garças sub-basin - Ribeiro, Victor Rodrigues [UNESP]; Ghilardi, Renato Pirani [UNESP]; FERREIRA DA SILVA CAMINHA, Silane Aparecida (UNESP - Universidade Estadual Paulista, 2019)
The Devonian of the Paraná basin is characterized by the consolidation of two sub-basins, one in the south called Apucarana sub-basin and another in the north called Alto Garças sub-basin. Paleoenvironmental differences are noted in both basins, in the Alto Garças sub-basin the differences are lateral: deltaic facies settled on the northern shore while marine facies reigned to the northwest. In the Jaciara-MT region, northwestern flank of the Alto Garças sub-basin, the outlying Devonian rocks were described only with open sea facies, however here we present new stratigraphic stacks, depositional environments and fossiliferous concentrations. Several depositional subunits were individualized, from the base to the top; facies of open sea with very representative fossils from the fauna Malvinokaffric (specimens of Lingulídeos, Orbiculoidea sp., Australocoelia sp., Notiochonetes sp. and Australospirifer sp.), facies from deltaic front influenced by the action of the tides, facies of incised valleys, facies of ruptures cyclic dikes of deltaic plains, fluvial facies, facies of marine transgressions. Bounded by Maximum Flood Surface, Forced Regression Surface and Transgressive Surface.
Fácies deltaicas devonianas de Jaciara-Mato Grosso: O indício de uma nova proposta estratigráfica para a sub-bacia de Alto Garças
Keywords: Alto Garças Sub-basin; Brazil; Devonian; Mato Grosso; Stratigraphy